Functional Limitations as Potential Mediators of the Effects of Self-Reported Vision Status on Fall Risk of Older Adults. (February 2015) - Steinman, Bernard A.; Allen, Susan M.; Chen, Jie; Pynoos, Jon
Objective: To test whether limitations in mobility and large-muscle functioning mediate self-reported vision status to increase fall risk among respondents age 65 and above.Method: This study used two waves from the Health and Retirement Study. We conducted binary logistic and negative binomial regression analyses to test indirect paths leading from self-reported vision status to falls, via indices of mobility and large-muscle functioning.Results: Limited evidence was found for a mediating effect among women; however, large-muscle groups were implicated as partially mediating risk factors for falls among men with fair self-reported vision status.Discussion: Implications of these findings are discussed including the need for prioritizing improved muscle strength of older men and women with poor vision as a preventive measure against falls.